Oxaliplatin-induced posterior reversible encephalopathy syndrome (PRES) - Janjua, Taimoor Khalid (BMJ Case Rep, 2017)
Posterior reversible encephalopathy syndrome (PRES), first introduced in 1996, is a neurotoxic state characterised by seizures, headache, vision change, paresis, nausea and altered mental status. Risk factors include hypertension, eclampsia/pre-eclampsia, infection/sepsis and cancer chemotherapy. Although exposure to toxic agents is a common occurrence in patients who develop PRES, oxaliplatin has rarely been associated with it, with only 10 cases reported worldwide. We present the case of an oxaliplatin-induced PRES in a 23-year-old male patient who was started on oxaliplatin/capecitabine as adjuvant chemotherapy for anal canal adenocarcinoma. The patient developed symptoms of headache, slurred speech and left-sided facial weakness on the ninth day after the first dose of oxaliplatin that lasted for 6–8 hours. The patient experienced another episode next day with similar symptoms that lasted for 8 hours. Oxaliplatin was withheld and the patient was discharged on capecitabine only. The patient had no new episodes since discharge on follow-up.